Knowledge, Attitudes and Practices of Skin Whitening Products Among Female University Students: A public Health Implication - Nadia Salem Alrawaiq; Amna Altaher Mohamed (Libyan Journal of Medical and Applied Sciences, 2025)
This study aimed to assess the knowledge, attitudes, and practices (KAP) related to skin whitening products among female university students and explore demographic factors associated with their use. A cross-sectional survey was conducted among 405 students across various academic disciplines. Descriptive statistics, chi-square test, t-test, logistic regression, and correlation analyses were performed to examine the KAP outcomes and their relationship to the characteristics of the population. The study found that 98.2% of respondents were aware of skin whitening agents, primarily through media (38%) and friends (32.8%). A notable 85.4% acknowledged potential side effects, and 72.3% could identify users based on specific traits. In terms of attitudes, only 43% believed environmental factors influenced skin whitening, while 45% disagreed. A substantial 42% viewed skin whitening as a beauty factor, with 29.1% believing it could lead to better treatment from others. Regarding practices, 53% of users had utilized these products for less than a year, with 40% applying them daily. Most users (74%) combined various agents, primarily creams (73.6%). While 75% were knowledgeable about potential side effects, misconceptions about addiction risk persisted. Younger age, medical and pharmacy education, and lack of awareness about side effects were significant indicator of product use. Higher frequency of use was positively correlated with greater satisfaction. This study highlights the need for targeted public health interventions to promote safer cosmetic practices, especially among young adults. Strengthening educational programs, regulating product safety, and addressing social and psychological drivers of skin whitening are crucial to mitigate the associated health risks.